Implications of the lack of permanent access to drinking water in the population, case municipality of Villavicencio 2016 (2017)
The present research work is about the description and analysis of the current situation of the main aqueduct system of Villavicencio; it is based on the existing regulations. The problem of the present investigation is determining the implications if the lack of permanent access to drinkable water for the population, with the objective of proposes definitive solutions adapted to the needs, that favor the development of the city and improve the level of quality of life of citizens. The investigation was done based on the methodology of case study, obtaining information from various sources like official websites of governmental entities, The information served to create conclusions oriented to the decision making, that makes more efficient the provision of the service of EAAV in Villavicencio.